Cement-stabilized Modified High Fines Melaka Series for Roadbases - Megat Mohd Noor, Megat Johari; Abdul Aziz, Azlan; Maail, Shukri (Universiti Putra Malaysia Press, 1995)
Roads are a crucial infrastructural element in the progress of a nation. Unavailability of suitable base materials causes total building cost to escalate. Strict adherence to standards to satisfy maximum working conditions would disregard the abundant supply of substandard materials. This paper discusses the potential exploitation of such substandard materials through modification of the strength characteristics. Rural and farm roads in developing countries are generally lightly trafficked, thus justifying a lower strength criterion (1.7 MN/m2 ) than normally adopted. Soils with high fines content are unsuitable for cement stabilization. The selected Melaka series was modified by the addition of river sand. Cement was subsequently added to the mixture and stabilized mechanically. Various soil sand-cement proportions were studied in terms of strength characteristics. A significant increase in strength, from 0.2 MN/mt to nearly 3 MN/m2, was noted with soil sand ratio of]:] with 12% cement content. This represents about a 14fold strength increase satisfying the current compressive strength of 2.8 MN/ mt for roadbases. The unit cost of producing the mixture was equivalent to supplying crusher run in a typical road project. The 1.7 MN/m2 criterion was met with a minimum cement content of 8% and a soil·sand ratio of 2:1. With 1.7 MN/m2 strength criterion, nearly 35% savings could be made by using the modified Melaka series soil instead of crusher run.